Role of microRNAs in skeletal muscle hypertrophy - Hitachi, Keisuke; Tsuchida, Kunihiro (Frontiers in Physiology, 2014)
Skeletal muscle comprises approximately 40% of body weight, and is important for locomotion, as well as for metabolic homeostasis. Adult skeletal muscle mass is maintained by a fine balance between muscle protein synthesis and degradation. In response to cytokines, nutrients, and mechanical stimuli, skeletal muscle mass is increased (hypertrophy), whereas skeletal muscle mass is decreased (atrophy) in a variety of conditions, including cancer cachexia, starvation, immobilization, aging, and neuromuscular disorders. Recent studies have determined two important signaling pathways involved in skeletal muscle mass. The insulin-like growth factor-1 (IGF-1)/Akt pathway increases skeletal muscle mass via stimulation of protein synthesis and inhibition of protein degradation. By contrast, myostatin signaling negatively regulates skeletal muscle mass by reducing protein synthesis. In addition, the discovery of microRNAs as novel regulators of gene expression has provided new insights into a multitude of biological processes, especially in skeletal muscle physiology. We summarize here the current knowledge of microRNAs in the regulation of skeletal muscle hypertrophy, focusing on the IGF-1/Akt pathway and myostatin signaling.